Conceptual design model of interactive television advertising: experts reviews on impulse purchase tendency - Che Omar, Azizah; Shiratuddin, Norshuhada; Sarif, Siti Mahfuzah; Abd Muin, Mohd Adib (WAIRCO Journal Publishers, 2015)
Previous studies have proposed factors of impulse purchase in different advertising mediums like website, mobile, traditional retail store and traditional television.However, to the best of researchers’ knowledge, none of the impulse purchase model is dedicated on impulse purchase tendency for interactive TV advertising. Therefore, a conceptual design model of interactive television advertising toward impulse purchase tendency (iTVAdIP) was developed. The focus of this study is to evaluate the conceptual design model of iTVAdIP through expert reviews. The finding showed that majority of the experts agreed that the conceptual design model is applicable to the development of iTV advertising and the model has the ability to increase impulse purchase level of iTV advertising.